Preference and palatability of indigenous and exotic acid soil-tolerant multipurpose trees and shrubs by West African Dwarf sheep - Kalio, G.A.; Oji, U.I.; Larbi, Asamoah (Springer, 2006)
Eleven acid soil-tolerant multipurpose trees and shrubs (MPTS) were assessed for preference and palatability with mature West African Dwarf (WAD) sheep using the cafeteria method. About 500 g each of the MPTS were weighed in triplicates into plastic feeding troughs and randomly placed around the perimeter of a Panicum maximum paddock (25 m × 25 m). Five ewes averaging 25.24 ± 0.69 kg were allowed 4 h access to the browse species daily for 12 d. Dry matter intake differed (p<0.05), ranging from 0.0 g in C. calothyrsus to 70.8 g in M. barterii. The number of animal visits, time spent and number of bites per visit on the browses also differed (p<0.05). There were positive correlations between DM intake and number of visits, number of bites, time spent on each fodder browsing and the coefficient of preference. The preference of the various MPTS by animals in descending order was M. barterii > A. cordifolia > L. leucoephala > B. monandra > D. guineensis > H. madagascariensis > T. tetraptera > T. africana > A. bella > B. grandiflora > C. calothyrsus.